Perancangan Sign System Pasar Rakyat Liluwo, Kota Gorontalo - Almer Hassan Ali; Muhammad Isla; Zulkifli L. Zain (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
The traditional market is a reflection of the application of a very basic populist economy. Where buying and selling transactions are carried out by the community mostly independently by managing available resources, which include the livestock sector, agriculture, crafts, food, services, and so on. At the Liluwo traditional market there are many sellers of various kinds of needs, ranging from basic household needs, clothing, prepared food and raw materials such as fish and vegetables, to hair cutting services. The facilities at the Liluwo traditional market are toilets, parking lots, prayer rooms. From the results of observations of researchers in the field, there has not been found a good sign system that helps make it easier for visitors. Some visitors, especially new prospective buyers, experience problems in finding a way/place to sell certain materials. From the problems mentioned above, the researchers plan to design a good sign system for the Liluwo traditional market to make it easier for buyers and sellers to carry out buying and selling activities. Apart from that, with a good sign system, the identity of the Liluwo traditional market will increase and can become an attraction in the eyes of the public.